2017
DOI: 10.21548/38-2-1605
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bioactive Compounds and Mineral Contents of Seedless Parts and Seeds of Grapes

Abstract: In this study, phenolic compounds, minerals, total flavonoids, total phenolic contents and antioxidant activities of the seedless parts (pulp+skin) and seeds of table and wine grapes were determined. Also, the total oil, tocopherol contents and fatty acid composition of seed oils of table and wine grapes were investigated. The highest total phenolic content of the grape pulp was found in Trakya ilkeren (199.063 mg/100 g), while total flavonoid and antioxidant activity of the pulp was determined at a high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
(33 reference statements)
4
17
1
Order By: Relevance
“…The values obtained for Ca and Mg were considerably lower than those found for K in all samples. In contrast, other authors found higher K and Ca content with respect to Mg in the grape seeds of different grape varieties from Turkey . The Ca content was between 3.16 and 4.05 mg g −1 for skins (Table ) and between 2.41 and 4.70 mg g −1 for seeds (Table ), with relatively similar values in all of the varieties that were studied, although Godello samples showed significantly lower content in seeds ( P < 0.001).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The values obtained for Ca and Mg were considerably lower than those found for K in all samples. In contrast, other authors found higher K and Ca content with respect to Mg in the grape seeds of different grape varieties from Turkey . The Ca content was between 3.16 and 4.05 mg g −1 for skins (Table ) and between 2.41 and 4.70 mg g −1 for seeds (Table ), with relatively similar values in all of the varieties that were studied, although Godello samples showed significantly lower content in seeds ( P < 0.001).…”
Section: Resultssupporting
confidence: 90%
“…Regarding the distribution of metals between skins and seeds within each variety (Tables and ), in general the total metal content in seeds was lower than in skins for all the elements, except for Ca and Mg in most samples. In contrast, other authors reported that the mineral content of grape seeds was higher than that found in other parts of the grape . In the case of Zn, the total content in seeds was slightly higher than that obtained in skins for most samples, except for Treixadura and Sousón varieties where the content in skins was between 1.2 and 1.6 times greater.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Grape ( Vitis vinifera L.) ranks among most important commercial fruit crops being grown and utilized around the globe since long (Al Juhaimi & Özcan, in press; Bail et al, ; Hussein & Abdrabba, ). The oil from grape seed is now becoming popular as a culinary oil due to the presence of specialty lipids and it may also serve as a good source of other nutritionally beneficial phytochemicals including phenol compounds, tocopherols, and fatty acids (Bail et al, 2008; Bjelica et al, ; Lutterodt, Slavin, Whent, Turner, & Yu, ; Geçgel et al, ; Ovcharova et al, ; Özcan, Al Juhaimi, Gülcü, Uslu, & Geçgel, ; Radovanovic, Dekic, & Radovanovic, ; Vujovic, Pejin, Popovic Djordjevic, Velickovic, & Tesevic, ). According to Wijendran and Hayes () and Beveridge, Girard, Kopp, and Drover (), oil from grape seeds contain unsaturated fatty acids, particularly oleic, and linoleic acids, which have been established to play vital role in cardiovascular health of humans.…”
Section: Introductionmentioning
confidence: 99%